Implementation of the Moral Education Cultivation Model in Islamic Boarding Schools in Deli Serdang Regency - Siregar, M Fajri Syahroni; Nasution, Wahyudin Nur; Nahar, Syamsu (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The aim of this research was carried out at the Mawaridussalam Islamic Boarding School and the Darul Arafah Raya Islamic Boarding School to analyze the planning of the Moral Education Model. Next, analyze the implementation of the Moral Education Model. Then to analyze the supporting and inhibiting factors in moral education and analyze the efforts made. This research includes a qualitative research methodology. This research includes field research, namely field research carried out in Islamic boarding schools. This research uses a phenomenological approach. To obtain data as research material, this was done by: interviews, observation (observing) and documentation studies. The data analysis methods used are data reduction, data display and conclusion drawing. Based on the research results, the planning for the moral education model that has been carried out by the Mawaridussalam modern Islamic boarding school and the Darularafah Raya Modern Islamic Boarding School has been prepared in such a way. Several models of moral education, researchers concluded that the Mawaridussalam modern Islamic boarding school and the Darularafah Raya Modern Islamic Boarding School use a structural model, due to the religious atmosphere presented in the Islamic boarding school environment due to the enthusiasm to carry out the Islamic boarding school regulations. The supporting factors are: environment good Islamic boarding school that is very conducive to instilling morals in students; Students who study and gain knowledge at the Mawaridussalam and Darul Arafah Raya modern Islamic boarding schools are based on their own interests and wishes, adequate facilities; There is cooperation. The inhibiting factors: the students themselves, there are students who are passive; Different environments and personalities. The efforts made by the Mawaridussalam Islamic Boarding School are to establish good relationships and collaborate with parents. Teachers have also tried to set a good example to the students. Regarding colleagues, the Islamic boarding school provides students with dormitories with the aim of maintaining Islamic brotherhood.